2018
DOI: 10.1246/cl.170967
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Selective Recognition of Sugars Using Lectin-inspired Temperature-responsive Polymers

Abstract: In this article, the selective recognition of sugars was investigated using lectin-inspired polymer which was composed of temperature-responsive polymer with sugar-binding benzoxaborole group. This polymer bound sugar selectively and showed excellent phase-transition behaviors dependent on the sugar type, concentration, and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Figure 2(a) shows the 1 H-NMR spectrum of the synthesized MAAmBO monomer in DMSO-d 6 solvent. Since the 1 H-NMR spectrum was found to be quite similar to previous studies [40,41], the signals at around 2.0 ppm, 5.0 ppm, 5.5~6.0 ppm, 7.3~8.0 ppm, 9.2 ppm, and 10.0 ppm were assigned to CH 3 group in methyl methacrylate (MAAm) (peak; a), CH 2 group in BO (peak; g), CH 2 group in MAAm (peak; b), phenyl groups in BO (peaks; d, e, f), amide group (peak; c), and OH group (peak; h), respectively.…”
Section: Characterization Of Maambo Poly[mpc] and Poly[mpc-co-maambo]supporting
confidence: 84%
“…Figure 2(a) shows the 1 H-NMR spectrum of the synthesized MAAmBO monomer in DMSO-d 6 solvent. Since the 1 H-NMR spectrum was found to be quite similar to previous studies [40,41], the signals at around 2.0 ppm, 5.0 ppm, 5.5~6.0 ppm, 7.3~8.0 ppm, 9.2 ppm, and 10.0 ppm were assigned to CH 3 group in methyl methacrylate (MAAm) (peak; a), CH 2 group in BO (peak; g), CH 2 group in MAAm (peak; b), phenyl groups in BO (peaks; d, e, f), amide group (peak; c), and OH group (peak; h), respectively.…”
Section: Characterization Of Maambo Poly[mpc] and Poly[mpc-co-maambo]supporting
confidence: 84%
“…[7][8][9] It is well known that boronic acids react with D-fructose selectively; however, it has been recently reported that D-allulose has higher affinity for boronic acids than D-fructose. 10,11 In particular, orthohydroxymethyl phenylboronic acid cyclic monoester (benzoxaborole, pK a B ¼ 7.34) 12 shows 12 times larger binding constant in the reaction with D-allulose than D-fructose, reported by Arimitsu et al 11 Hence, using benzoxaborole as the reaction site is expected to enable highly sensitive and selective sensing of Dallulose.…”
Section: Introductionmentioning
confidence: 96%
“…The members of the second category have also wide varieties but characteristics, which include polymers responding to light irradiation, 12,13 magnetic fields, 14,15 mechanical forces, 16,17 and other stimuli. In addition to these "physical" stimuli, stimuli that respond to "specific molecules" such as CO 2 , 18 H 2 O, [19][20][21][22] glucose, 23,24 monosaccharides, 25 and enzyme, 26 are also splendidly exploited and incorporated into the synthetic polymer matrix. A complex system in which polymers change their stimuli-responsive properties in response to another stimulus has also been developed.…”
Section: Introductionmentioning
confidence: 99%